Micro-RNAs 518d-3p and 618 Are Upregulated in Individuals With Type 1 Diabetes With Multiple Microvascular Complications - Santos-Bezerra, Daniele P.; Santos, Aritania S.; Guimarães, Gabriel C.; Admoni, Sharon N.; Perez, Ricardo V.; Machado, Cleide G.; Pelaes, Tatiana S.; Passarelli, Marisa; Machado, Ubiratan F.; Queiroz, Marcia S.; da Silva, Maria Elizabeth R.; Correa-Giannella, Maria Lucia (Frontiers in Endocrinology, 2019)
OBJECTIVE To compare the serum micro-RNAs (miRNAs) profile of individuals with type 1 diabetes without microvascular complications versus those with multiple severe microvascular complications, in order to identify epigenetically modulated pathways in these two groups of individuals. RESEARCH DESIGN AND METHODS A total of 10 subjects was selected among individuals followed in the Diabetes Outpatient Clinic and sorted according to the absence or presence of all microvascular complications. Samples from these participants were used for evaluation of serum miRNA expression profile employing a qRT-PCR assay with hydrolysis probes based on the Taqman Low Density Arrays (TLDA) system. The top six most differentially expressed miRNAs between the aforementioned groups were validated by qRT-PCR in additional 47 type 1 diabetes individuals sorted according to the absence or presence of all microvascular complications and matched for age, sex, degree of metabolic control, diabetes duration, and age at diagnosis. RESULTS 21 out of 377 miRNAs were upregulated in the group of individuals with all microvascular complications versus the group without complications. The following miRs were validated: 518-3p, 34a-5p, 126-5p, 425-5p, 618 and 139-5p and logistic regression analyses showed that miRNA-518-3p and miRNA-618 were positively associated with multiple microvascular complications after adjustment for age, sex, diabetes duration, HbA1c and use of statin, angiotensin-converting enzyme inhibitors and amlodipine. CONCLUSIONS In this cohort of type 1 diabetes individuals, serum miR-518d-3p and miR-618 were upregulated in those with diabetes kidney disease, diabetes retinopathy, peripheral neuropathy and cardiovascular autonomic neuropathy in comparison to individuals with no microvascular complications.